Mobile Applications for Smart and Agile Enterprise Management - Filipowska, Agata; Żurawski, Piotr (Studia Oeconomica Posnaniensia, 2015)
The article discusses the capabilities of a mobile application being a client to an ERP system to meet the needs of smart and agile enterprise management. The article discusses the function of ERP systems, their evolution and presents an overview of the current market of ERP systems (in Poland and worldwide). I It then discusses the differences between desktop and mobile applications, especially concerning their usability. The article concludes with a case study presenting a comparative analysis of mobile and desktop applications for the sales area.